INTRODUCTION TO VOLUME 12 : 2014 - Mohd Noordin, Nazri (PLANNING MALAYSIA, 2016)
MIP is once again proudly to riposte its eleventh volume of Planning Malaysia. Since its inception in 2003, the Journal was well-received by the members as well as the academic fraternity. This is due to perhaps, the awareness for knowledge seeking and improvement among the members as the articles touch on wide spectrum of our daily planning issues. It is indeed a great achievement to the Institute as we strive to encourage more members and academics to write and share new ideas on planning and urban development. Urban and Regional Planning is very broad based subject that covers technical and political process concerned with the control of the use of land and design of the urban environment, including transportation networks, to guide and ensure the orderly development of settlement and communities. The wide ranging topics in this issue reflect the various dimensions of sustainable cities and urban planning that is holistic and comprehensive. One of the key objectives of this issue is to provide a platform for town planners to share new ideas and experiences on cities and urban planning. Such new ideas are by research, studies undertaken or actual hands-on experiences of planners. Thus I hope this issue provides a better insight to all readers of the broad dimensions that urban or town planning has and the role of town planners play in growth and development of the nation. Apart from the MIP’s contribution to the planning circle, Planning Malaysia is also extended to various planning related organizations, institutions of higher learning as well as to all members of the institute. We anticipate to eventually extending the circulation of this journal to non-planning related organizations and institutions that has an indirect role in planning within and outside the country. We hope this issue will serve the purpose and welcome any feedback for the improvement in the forthcoming issue. As a new preside President, I would like to acknowledge and congratulate the new journal’s Editor-in-Chief, Professor Dato’ Dr. Mansor Ibrahim and his team for the dedication and continuous support to the Institute. Thank you and happy reading.